4(2b+6)+11=-8b-13

Simple and best practice solution for 4(2b+6)+11=-8b-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2b+6)+11=-8b-13 equation:


Simplifying
4(2b + 6) + 11 = -8b + -13

Reorder the terms:
4(6 + 2b) + 11 = -8b + -13
(6 * 4 + 2b * 4) + 11 = -8b + -13
(24 + 8b) + 11 = -8b + -13

Reorder the terms:
24 + 11 + 8b = -8b + -13

Combine like terms: 24 + 11 = 35
35 + 8b = -8b + -13

Reorder the terms:
35 + 8b = -13 + -8b

Solving
35 + 8b = -13 + -8b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '8b' to each side of the equation.
35 + 8b + 8b = -13 + -8b + 8b

Combine like terms: 8b + 8b = 16b
35 + 16b = -13 + -8b + 8b

Combine like terms: -8b + 8b = 0
35 + 16b = -13 + 0
35 + 16b = -13

Add '-35' to each side of the equation.
35 + -35 + 16b = -13 + -35

Combine like terms: 35 + -35 = 0
0 + 16b = -13 + -35
16b = -13 + -35

Combine like terms: -13 + -35 = -48
16b = -48

Divide each side by '16'.
b = -3

Simplifying
b = -3

See similar equations:

| 1/3x^2+4x-3=0 | | 3x-6=2x+2 | | 14j-6+8j-5= | | 3n-2+2n+5= | | 0=3b+27 | | a+2/a-1=a+11/a+4 | | b+12=-21 | | 1-2c-3c+100= | | 9y-8+4y= | | 3x/x^2 | | 9/540 | | ln(3x^2)-2x=0 | | 26+48x=-502 | | X=6-21 | | 10=n/6+9 | | -3(2t-2)+4t=7t-8 | | 6/174 | | 2/194 | | -0.5=-2x+8.1 | | 8/668 | | 18-33x=180 | | -3y-2y-y= | | 3/237 | | 3/261 | | 4a+5-a+2= | | 8z-z=-2+2z-1-2 | | 7/336 | | 9/603 | | 9t+5t-3t= | | 6/504 | | 28-4d=59-17 | | 7/322 |

Equations solver categories